2020
DOI: 10.5194/bg-2020-1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactive impacts of meteorological and hydrological conditions on the physical and biogeochemical structure of a coastal system

Abstract: <p><strong>Abstract.</strong> The German Bight was exposed to record high riverine discharges in June 2013, as a result of flooding of the Elbe and Weser rivers. Several anomalous observations suggested that the hydrodynamical and the biogeochemical state of the system was impacted by this event. In this study, we developed a biogeochemical model and coupled it with a previously introduced high resolution hydrodynamical model of the southern North Sea, in order to bett… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Furthermore, in their recent study, Kerimoglu et al. (2020) confirmed the effect of wind fields on the stratification of the GB during the 2013 extreme event, by simulating the hydrodynamics of the GB under different forcing scenarios. In the present study, a different approach is taken by evaluating the processes that contribute to the increase and decrease of stratification when the position of the river plume changes (section 4.3.1).…”
Section: Results: Stratification In the Gb During The Extreme River Dmentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, in their recent study, Kerimoglu et al. (2020) confirmed the effect of wind fields on the stratification of the GB during the 2013 extreme event, by simulating the hydrodynamics of the GB under different forcing scenarios. In the present study, a different approach is taken by evaluating the processes that contribute to the increase and decrease of stratification when the position of the river plume changes (section 4.3.1).…”
Section: Results: Stratification In the Gb During The Extreme River Dmentioning
confidence: 83%
“…Kerimoglu et al. (2020) have shown that these can be improved by extensive tuning of the horizontal diffusion.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The deeper northern part of the North Sea experiences seasonal stratification as summertime warming of the surface establishes a strong pycnocline (Wakelin et al 2012), while the shallower southern part is typically permanently mixed due to strong tidal forcing (Bozec et al 2005). More recent studies have defined biome boundaries on an even finer scale depending on the stratification regime and on the freshwater influence on biogeochemical processes showcasing the high spatial variability in the North Sea (van Leeuwen et al 2015; Kerimoglu et al 2020). While the Lysbris FerryBox‐MBS p CO 2 measurements are available over a large area of the North Sea, in order to check and validate the long‐term MBS p CO 2 record, we focus on the small restricted box in the Skagerrak where many crossovers with the SHS system on Nuka Arctica were identified.…”
Section: Resultsmentioning
confidence: 99%